Horner's syndrome secondary to internal carotid artery occlusion. Issue 2 (4th February 2021) - Saleemi, Saadat Ali; Sahathevan, Ramesh
Abstract : Horner's syndrome results from interruption of the sympathetic innervation to the eye. This interruption may occur at three anatomical levels along the sympathetic trunk pathway. There are numerous causes of Horner's syndrome, including injury to the carotid artery, of which arterial dissection is the commonest pathology. Occlusive carotid disease secondary to atherosclerosis is a relatively rare cause of Horner's syndrome. We describe a patient with Horner's syndrome due to complete occlusion of the ipsilateral internal carotid artery.